1040 The emergency laparotomy collaborative: scaling up an improvement bundle for high risk surgical patients. (21st November 2017) - Peden, Carol; Aggarwal, Geeta; Quiney, Nial; Pullyblank, Anne; Stephens, Tim
Abstract : Background: Emergency intra-abdominal laparotomy is a common surgical procedure. Mortality is high with 11%–15% of patients dying within 30 days of surgery. Complication rates are also high and >25% of patients remain in hospital for >20 days. A previous study, ELPQuIC, successfully used a care bundle to reduce mortality in four hospitals. Objectives: The aim of the Emergency Laparotomy Collaborative was to scale implementation of the ELPQuIC bundle to 24 NHS Trusts within three Academic Networks to reduce mortality, complications and length of stay. Methods: We used the IHI Breakthrough Series Collaborative Model to bring 100+ staff together over two years with 5 large events and 4 local quality improvement events. Data collection was through the National Emergency Laparotomy Audit (NELA). Economic analysis was undertaken. Using NELA data we distributed comparative dashboards showing care bundle adherence and patient outcomes quarterly. The collaborative model enabled Trusts to share progress through dialogue, group reflection and celebration of success. Results: 5793 patients had an emergency laparotomy between October 2015 and December 2016. Crude mortality decreased from 9.8% to 8.7% and length of stay decreased by 1.3 days. There were significant improvements in delivery of care bundle components. Economic analysis showed potential savings of £2 M in 15 months, primarily through decreased length of stay. The collaborative promoted innovation with ideas such as 'virtual peer review' emerging. Conclusions: Implementation of the ELPQuIC care bundle improved process delivery resulting in better outcomes for emergency laparotomy patients across 25 NHS Trusts. QI promotion through a BTS model fostered collaboration and innovation. References: 1. National Emergency Laparotomy Audit. The Second Patient Report 2016. Availablefrom NELA 2016. http://www.nela.org.uk/reports. 2. Al-Temimi, Griffee M, Ennis TM et al. When is death inevitable after emergency laparotomy? Analysis of the American College of Surgeons National Surgical Quality Improvement Program database. J Am Coll Surg 2012;215:503–11. 3. Saunders D, Murray D, Varley S, Pichel A, Peden CJ. Variations in mortality after emergency laparotomy: the first report of the UK Emergency Laparotomy Network. BJA 2012;109:368–375. 4. Huddart S, Peden CJ, Swart M et al. Use of a pathway quality improvement care bundle to reduce mortality after emergency laparotomy. BJS 2015;102:57–66.